Use of an extrapolation method to estimate the population of cats and dogs living at homes in Mexico in 2022. - Irais Peña-Corona, Sheila; Gomez-Vazquez, Jose Pablo; Aditi López-Flores, Evelyn; Vargas Estrada, Dinorah; Arvizu-Tovar, Laura Olivia; Pérez-Rivero, Juan José; Juárez Rodríguez, Ivan; Sierra Resendiz, Alonso; Soberanis-Ramos, Orbelin (Veterinaria México OA, 2022)
Cats and dogs have a very close relationship with humans. Currently, the overpopulation of these species in various countries worldwide has been identified as a severe public health problem. To establish effective programs for population control, it is necessary to estimate the number of cats and dogs. To our knowledge, there are no studies that assess the number of canine and feline population by state in Mexico. Therefore, this study aimed to estimate the canine and feline population living at homes using official information reported by the National Institute of Statistics, Geography and Informatics [Instituto Nacional de Estadística Geografía e Informática] through a constant-share model, a ratio extrapolation method. The estimated dog population living at homes was 42 625 010 dogs and 7 346 925 cats (at least 5.8 times less than the number of dogs). By 2022, the Mexico's estimated human:dog ratio was 2.4:1, and the human:cat ratio 17.6:1. The Estado de México had more than six million dogs and 962 177 cats. Colima had the smallest estimated dog population (245 489), and Baja California Sur the smallest estimated cat population (slightly over 30 000). Health authorities and veterinary practitioners should promote responsible ownership to increase veterinary care and control the birth of dogs and cats.